NONLINEAR ABSORPTION OF SUPERSTRONG CIRCULARLY POLARIZED LASER RADIATION IN PLASMA OWING TO INVERSE BREMSSTRAHLUNG ON COULOMB CENTERS - A. G. Ghazaryan
Nonlinear absorption of circularly polarized ultrastrong laser radiation in plasma through the induced bremsstrahlung of electrons on Coulomb centers in the scope of low-frequency approximation is investigated based on the numerical simulations. We study the cases of isotropic and anisotropic distributions of plasma electrons over the momenta and show that for both cases the coefficient of nonlinear absorption is inversely proportional to the wave intensity. Coefficient of nonlinear absorption of relativistic Maxwellian plasma at high temperatures of electrons is considered.
Keywords: Physics